2008
DOI: 10.1186/1471-2415-8-8
|View full text |Cite
|
Sign up to set email alerts
|

Rotational stability of the AcrySof SA60TT toric intraocular lenses: A cohort study

Abstract: Background: To evaluate the rotational stability of the three types of AcrySof SA60TT toric intraocular lenses (Alcon, Switzerland) in cataract surgery after the first postoperative week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
43
1
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 12 publications
5
43
1
7
Order By: Relevance
“…The results of our study corroborate previous studies, 11 which demonstrates that proper selection and preoperative examination of patients followed by uncomplicated IOL implantation of one-piece hydrophobic acrylic toric IOLs results in acceptable stability and visual outcome.…”
Section: Discussionsupporting
confidence: 90%
“…The results of our study corroborate previous studies, 11 which demonstrates that proper selection and preoperative examination of patients followed by uncomplicated IOL implantation of one-piece hydrophobic acrylic toric IOLs results in acceptable stability and visual outcome.…”
Section: Discussionsupporting
confidence: 90%
“…The percentage of patients with IOL rotation <10° on two similar to our 91.6%, varying between 96.7 and 100%. [1][2][3][4][5] In conclusion, Acrysof ® T3, T4 and T5 thoric lens implants allow the correction of presurgery astigmatism with a high percentage of success in what concerns NCVA and residual postsurgery astigmatism, with a minimum degree of lens axis rotation after 2-6 months according to the published series. [1][2][3][4][5][6] The minor of modification of the surgical procedure and a broad dissemination of the necessary presurgery diagnostic devices, many of which are mainstream, lead us to consider a higher degree of utilization of this type of lenses in the mid term for patients with significant presurgery astigmatism intervened for cataracts.…”
Section: Discussionmentioning
confidence: 89%
“…Several authors have utilized IOL Master in in their studies, although others have utilized systems such as Orbscan II (Bausch & Lomb, Rochester, NY, USA) or conventional keratometres to obtain the K values. [2][3][4] In what concerns the determination of the 0°-180° axis, the system utilized by the FDA and the authors was dermographic marking with slit lamp while in this study the Elies marker was utilized (E. Janach, Como, Italy). The results of these studies in what concerns the lens rotation degree are slightly lower than our 3.87°±3.25 values, varying in a range of 2.2° to 3.75°, which is quite consistent with our data.…”
Section: Discussionmentioning
confidence: 99%
“…Rotation misalignment was 10° or less in 97% patients and 5° or less in 81% patients. Zuberbuhler et al (27) subsequently reported a large series of AcrySof SN60T toric IOLs in 44 eyes. The mean toric IOL axis rotation was 2.2 ± 2.2°, and 95%IOL were within 5° of the targeted axis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were comparable with those in studies of the AcrySof toric IOL. Intraoperative positioning of toric IOLs with greater accuracy was necessary to achieve the most optimum cylinder correction in all patients (21,26,27) . The Rayner M-flex T is a refractive toric multifocal IOL with a multizone design that can cause loss of contrast sensitivity because of the distribution of total available light between several focal points.…”
Section: Discussionmentioning
confidence: 99%